(untitled) (Journal of the College of Education for Women, 2019)
Of good reasoning (the art of unique moral turn him poets of Andalusia inpoetry verse emitter myself, and to achieve a very technical. Either the emitter isrelated to the nature of the environment and the composition of personal Andalusiaof appetite for life and interaction with the legibility beautiful, and it was (wit)feature in them even said they are charming as Bagdad ions , and either art, it madethem this color to show their ability intellectual in the search for bugs, andstimulate their imaginations in a contract equations in the interpretation and findjustifications for the ideas and meanings Exaggeratedly times, and especially in thepurpose of praise, and novelty in many cases, as in the spinning and AlEkhwaniat,in the language of affordable and methods Miscellaneous: The question ofemphasis and dialogue, has been hired to the achievement of poetic analogy isrepresentative and diagnostic metaphor, and antagonism which are distributedeither on both sides of the House poetry alluded to the human side, including theconflict between reality and the practitioner.As if this art was expressed mostly by the desire of decorated lattice, andintellectual luxury commensurate with the ornament of life Andalusia, and wasprobably an outlet in some cases is the ambition to his society, as in both cases wasintended to give the forum, surprising and extraversion and pleasure includingdevised sense of the strange or adorable fiction.